RELIGIOUS RATIONALIZATION AND ITS ROLE FOR THE EMERGENCE OF MODERN EDUCATIONAL INSTITUTIONS - Dodonova, Vira (Educological discourse, 2017)
The article is devoted to the analysis of the general pattern of the historical development of Western society, which consists in a gradual increase in the trend of rationalization. Under rationalization is understood the process of gradual replacement of random, situational, openly irrational motives of human actions into logical, predicted, wholerelevant. An understanding of the rationalization and "disenchantment of the world" by M. Weber explores the essence of the modernist project as a "disenchantment" of social relations. At the same time, "disenchantment" was understood by them not only as the liberation of society from the rule of magic and superstition. "Disenchantment" is the growth of trust in the mind, science, education, rational procedure in all manifestations of social life, which is the leading trend and the internal meaning of the entire era of modernity. The role of "religions of salvation" is clarified to form integral pictures of the world not only for the religious outlook, but also for the born philosophical systems. It turns out that religious rationalization was only the beginning of the universal process of rationalization of social relations. A consequence of this trend is the differentiation of value spheres and the emergence of New European social institutions: the market, law, bureaucracy etc. Modern transformations are made possible through religious rationalization and secularization. The role of scientific rationality as an educational reference point in the Enlightenment is researched. During this time the school begins to draw knowledge not from the religious tradition, but from science. The importance of religious rationalization for the emergence of modern educational institutions, including secular schools and universities.